Wheeled Mobility Biomechanics - Philip Santos Requejo (Frontiers Research Topics, 2016)
For the manual wheelchair (MWC) user, loss of lower extremity function often places the burden for mobility and activities of daily living on the upper extremities. This e-book on Wheeled Mobility Biomechanics contains current research that provides insights into the mechanical demands and performance techniques during tasks associated with MWC. Our intent was to contribute to advancing the knowledge regarding the variables that promote or hinder an individual's capacity to handle the daily manual wheeled mobility demands and gain greater insights into upper extremity loading consequences, predictors of pain onset and injury, and ultimately identify strategies for preserving health and functional mobility for the MWC user.